Health Sector Portfolio Optimization Using the Markowitz Approach with Risk Aversion and Risk Tolerance Parameters - Ismail, Muhammad Iqbal Al-Banna; Pirdaus, Dede Irman (Operations Research: International Conference Series, 2024)
This study analyzes the optimal portfolio formation of health sector stocks listed on the Indonesia Stock Exchange using the Markowitz approach with dual risk parameters. Unlike traditional mean-variance optimization, this research incorporates both risk aversion (ρ) and risk tolerance (τ) parameters to better accommodate varying investor risk preferences. Using daily closing price data from six health sector stocks during the period January 2022 to December 2023, this study employs web scraping techniques for data collection and implements portfolio optimization calculations. The results show that the dual risk parameters approach produces consistent portfolio weights across both risk measures, with SIDO.JK receiving the highest allocation (approximately 41.6%) followed by SOHO.JK (23.0%) and SILO.JK (16.9%). The efficient frontier analysis demonstrates portfolio risk ranges from 0.015 to 0.030 with returns between 0.10% to 0.45%. This study contributes to the literature by demonstrating how incorporating dual risk parameters can provide more nuanced portfolio allocations while maintaining the fundamental benefits of diversification.